Primary Non-Adherence to Antihistamines—Conclusions From E-Prescription Pilot Data in Poland - Kardas, Grzegorz; Panek, Michał; Kuna, Piotr; Cieszyński, Janusz; Kardas, Przemysław (Frontiers in Pharmacology, 2020)
Background: In allergic conditions such as allergic rhinitis and urticaria, orally administered H1-antihistamines belong to first-line therapy and therefore, are widely prescribed. Due to the frequent, and often chronic, course of allergic diseases, adherence is of great importance. In 2018 a novel, nationwide e-prescription system was piloted in Poland, which allowed to analyse primary non-adherence to orally administered H1-antihistamines. Objectives: To assess the primary non-adherence to orally administered H1-antihistamines in Poland, defined as not redeeming the drug issued on a particular e-prescription within its validity period. Methods: The study was based on all e-prescriptions issued in Poland in 2018, issued for 119.880 drugs. The analysis included 9 major orally administered H1-antihistamines available in Poland. Results: Out of 2280 analysed e-prescriptions on orally administered antihistamines, 1803 (79.1%) of them were redeemed. Therefore, the level of primary non-adherence reached 21%. Among women it reached 19,9%, but it was not significantly lower than among men (23.4%, p=0,064). The highest non-adherence (31.3%) was observed in the age group 19-39, whilst the highest adherence rate (84.6%) was observed in those aged 75+.The most frequently prescribed second-generation antihistamine was bilastine – 596 e-prescriptions with 23.7% primary non-adherence. Conclusions: More than 1 out of 5 e-prescriptions on orally administered H1-antihistamines were not redeemed in Poland in 2018. Age, but not gender, significantly influenced the degree of primary non-adherence to these drugs. To authors knowledge, this is the first real-life study on primary non-adherence to H1-antihistamines in Poland and one of the very few on this subject worldwide.